Positive electrode sheet and preparation method thereof and laminated lithium battery

By opening a thin groove on the edge of the active layer of the positive electrode sheet of the lithium-ion soft-packed lithium battery, a small thickness area is formed, and the edge NP ratio is increased, the problem of lithium and drum edges after the lithium battery cycle is solved, and the circulation of the battery is improved and safety performance.

CN118899397BActive Publication Date: 2025-01-17JIANGSU PYLON BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411377085.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-17
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Lithium-ion soft-pack laminated lithium batteries are prone to edge lithium decomposition and drumming problems after high cycle times, which are difficult to completely solve in the existing technology, and there are errors in the control of the electrolyte dosage, which affects the cycle performance and safety performance of the battery.

Method used

A positive electrode sheet is designed, and its active layer includes a normal thickness region and a small thickness region. By opening a thin groove at the edge of the active layer, the thinning depth ratio coefficient is within the range of 8.5% to 12%, and the edge NP is increased To improve edge lithium and drum edge problems.

Benefits of technology

The thinning design reduces the edge thickness, effectively improves the lithium edge and drum edge problems after the lithium battery cycle, improves the cycle performance and safety performance of the battery, and is easy to operate and controllable capacity loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118899397B_ABST
    Figure CN118899397B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of battery preparation, and discloses a positive electrode sheet, a preparation method thereof, and a laminated lithium battery. The positive electrode sheet of the laminated lithium battery includes a current collector and an active layer arranged on two opposite sides of the current collector; each active layer includes a normal thickness area and a small thickness area, the small thickness area is located at the edge of the active layer, and the thickness of the normal thickness area is greater than the thickness of the small thickness area. The preparation method of the positive electrode sheet of the laminated lithium battery comprises: a thinning groove is opened on each side of the active layer of the positive electrode sheet obtained after rolling, and the corresponding part of the thinning groove will be used to form a small thickness area; the thinning groove includes an edge thinning groove and a middle thinning groove; punching is performed along the length direction of the middle thinning groove to obtain a plurality of finished positive electrode sheets. The preparation method is simple to operate and has high preparation accuracy. The prepared positive electrode sheet can effectively improve the problems of edge lithium deposition and bulging edges of the laminated lithium battery after cycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery preparation, and in particular to a positive electrode sheet and a preparation method thereof, and a laminated lithium battery. Background Art

[0002] Lithium-ion soft-pack laminated lithium batteries have the advantages of long cycle life and no memory effect, but after a high number of cycles, edge lithium deposition and the resulting bulging problem will occur, affecting the battery's cycle performance and safety performance. The formation of edge lithium deposition is related to factors such as the N / P ratio of the active material and the lithium ion enrichment of the electrolyte. The main solution is generally to control the amount of electrolyte: it mainly focuses on the calculation of the porosity of the material to obtain the optimal electrolyte injection amount to avoid electrolyte enrichment at the edge of the lithium battery electrode. The actual error is large, and less electrolyte causes the battery to be harder, the electrolyte infiltration is poor, and local electrolyte enrichment is inevitable.

[0003] The existing solutions cannot completely eliminate the bulging problem caused by lithium deposition on the edges of lithium batteries after a high number of cycles. The amount of electrolyte used to control lithium deposition on the edges is greatly affected by the materials, and high battery consistency requirements are imposed. Local accumulation of electrolyte is inevitable. It is easy to cause insufficient electrolyte use, and the electrolyte infiltration time for the positive and negative electrodes is prolonged. The battery is too hard and prone to appearance abnormalities and other problems.

[0004] Therefore, it is of great significance to develop a stable, controllable, easy-to-use pole piece and its processing technology that can improve the lithium deposition at the edge of the lithium-ion soft-pack stacked lithium battery cycle process and the bulging edge caused by it.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a positive electrode sheet and a preparation method thereof and a laminated lithium battery, aiming to improve at least one problem mentioned in the background technology.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a positive electrode sheet of a laminated lithium battery, comprising a current collector and an active layer disposed on two opposite sides of the current collector;

[0009] Each active layer includes a normal thickness region and a small thickness region, the small thickness region is located at the edge of the active layer, and the thickness of the normal thickness region is greater than that of the small thickness region;

[0010] The width of the small thickness area is 4~6mm.

[0011] The difference between the normal thickness area and the small thickness area is H=k(ab) / 2, where a is the thickness of the positive electrode sheet in the normal thickness area, b is the thickness of the current collector, and k is the thinning depth proportional coefficient;

[0012] k=[(A1*w1*R1) / (A2*w2*R2)]*[1-(S0*(1-1%)-S1) / S2], A1 is the negative electrode surface density, unit mg / cm 2 ; w1 is the proportion of negative electrode active material; R1 is the negative electrode capacity in gram, unit is mAh / g; A2 is the surface density of the positive electrode unthinned area, unit is mg / cm 2 ; w2 is the proportion of positive electrode active material; R2 is the positive electrode capacity in grams, unit mAh / g; S0 is the active layer area of ​​the positive electrode sheet, unit mm 2 ; S1 is the normal thickness thinning area, unit: mm 2 ; S2 is the area of ​​the small thickness region, unit: mm 2 .

[0013] In an optional embodiment, the designed NP ratio of the positive electrode sheet is 1.1~1.5.

[0014] In an optional embodiment, the difference in thickness between the normal thickness area and the small thickness area is H=k(ab) / 2, where a is the thickness of the positive electrode sheet in the normal thickness area, b is the thickness of the current collector, and k is the thinning depth proportional coefficient, which is 8.5%~12%.

[0015] In a second aspect, the present invention provides a method for preparing a positive electrode sheet of a laminated lithium battery as in any one of the aforementioned embodiments, comprising: opening a thinning groove on each active layer of the positive electrode sheet obtained after rolling, wherein the thinning groove corresponding to the thinning groove is used to form a small thickness area;

[0016] The skived grooves include edge skived grooves and middle skived grooves, wherein the edge skived grooves are located at the edges of the active layer of the primary positive electrode sheet, and the middle skived grooves are located at the non-edges of the primary positive electrode sheet;

[0017] Punching is performed along the length direction of the middle thinning groove to obtain multiple finished positive electrode sheets.

[0018] In an optional embodiment, the width of the edge thinning groove is 4-6 mm; the width of the middle thinning groove is 8-12 mm.

[0019] In an optional embodiment, the punching is performed along the center line of the middle thinning groove.

[0020] In an optional embodiment, the shape of the middle thinning groove visible on the surface of the active layer is a rectangle, and the shape of the cross section of the middle thinning groove perpendicular to the surface of the active layer is a rectangle, an isosceles triangle, a semicircle or a semi-ellipse.

[0021] In a third aspect, the present invention provides a laminated lithium battery, comprising a positive electrode sheet according to any one of the aforementioned embodiments or a positive electrode sheet prepared by the preparation method according to any one of the aforementioned embodiments.

[0022] The present invention has the following beneficial effects:

[0023] The positive electrode sheet provided by the present invention has a smaller thickness at the edge of the active layer than at the non-edge. In the range of edge lithium deposition in the later stage of the cycle, the thickness of the edge is reduced by thinning design, so that a slightly larger edge NP ratio suitable for the later stage can be obtained, which can effectively improve the problems of edge lithium deposition, bulging edge, etc. after the cycle of the laminated lithium battery.

[0024] The preparation method provided by the present invention increases the edge NP ratio by opening thinning grooves on the initial positive electrode sheet after rolling, and has the characteristics of easy operation and construction; the method can improve the lithium deposition and bulging problems by sacrificing a small amount of capacity; because the thickness of the active layer will no longer change after rolling, the thinning of the active layer after rolling also has the characteristic of controllable thinning accuracy, so the preparation method provided by the embodiment of the present invention can effectively improve the lithium deposition and bulging problems of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 Three views of the positive electrode sheet provided in the embodiment of the present invention, including a main view on the upper left, a side view on the upper right, and a bottom view below;

[0027] Figure 2 This is a front view of a thinning groove formed on a primary positive electrode sheet;

[0028] Figure 3 A bottom view showing a thinning groove formed on a primary positive electrode sheet;

[0029] Figure 4 A schematic diagram of opening a middle thinning groove with an inverted triangle cross section on the active layer of a primary positive electrode sheet;

[0030] Figure 5 This is a schematic diagram of opening a middle thinning groove with a semicircular cross-section on the active layer of a primary positive electrode sheet.

[0031] Icons: 10-positive electrode; 11-current collector; 12-active layer; 12a-normal thickness area; 12b-small thickness area;

[0032] 100-initial positive electrode sheet; 111-edge thinning groove; 112-middle thinning groove. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] The positive electrode sheet 10 and its preparation method and the laminated lithium battery provided in the embodiment of the present invention are described in detail below.

[0035] like Figure 1 As shown, a positive electrode sheet 10 of a laminated lithium battery provided in an embodiment of the present invention comprises a current collector 11 and an active layer 12 arranged on two opposite sides of the current collector 11;

[0036] Each active layer 12 includes a normal thickness region 12 a and a small thickness region 12 b . The small thickness region 12 b is located at the edge of the active layer 12 . The thickness of the normal thickness region 12 a is greater than that of the small thickness region 12 b .

[0037] The thickness of the positive electrode sheet 10 provided by the present invention is smaller at the edge of the active layer 12 than at the non-edge. In the range of edge lithium deposition in the later stage of the cycle, the thickness of the edge is reduced by thinning design, so that a slightly larger edge NP ratio suitable for the later stage can be obtained, which can effectively improve the problems of edge lithium deposition and bulging edge of the laminated lithium battery after the cycle.

[0038] Optionally, in order to avoid capacity loss and improve edge lithium deposition, bulging and other problems, the width L1 of the small thickness area 12b is 4-6 mm. This width value is based on the initial swelling range of the battery, which is about 4-6 mm, so the width is taken to correspond to it.

[0039] Optionally, the difference between the normal thickness region 12a and the small thickness region 12b is H=k(ab) / 2, where a is the thickness of the positive electrode sheet 10 in the normal thickness region 12a, b is the thickness of the current collector 11, and k is the thinning depth proportionality coefficient;

[0040] k=[(A1*w1*R1) / (A2*w2*R2)]*[1-(S0*(1-1%)-S1) / S2], A1 is the negative electrode surface density, unit mg / cm 2 ; w1 is the proportion of negative electrode active material; R1 is the negative electrode capacity in gram, unit is mAh / g; A2 is the surface density of the positive electrode unthinned area, unit is mg / cm 2 ; w2 is the proportion of positive electrode active material; R2 is the positive electrode capacity in grams, unit mAh / g; S0 is the active layer area of ​​the positive electrode sheet, unit mm 2 ; S1 is the normal thickness thinning area, unit: mm 2; S2 is the area of ​​the small thickness region, unit: mm 2 .

[0041] The length and width of the positive electrode sheet are known. Once the width L1 of the small thickness area is determined, S1 and S2 can be determined.

[0042] When the difference between the thickness of the normal thickness area and the small thickness area meets the requirements of the above formula, it can better improve the problems of lithium deposition and bulging edge.

[0043] Optionally, the design NP ratio of the positive electrode sheet is 1.1~1.5. The NP ratio refers to the ratio of the reversible surface capacity of the negative electrode (Negative) and the positive electrode (Positive) inside the battery. Usually the design range of the NP ratio is generally 1.1~1.5. Of course, it should be noted that in the present application, due to the different thickness at the edge and the non-edge, the design NP ratio is different from the actual NP ratio. In the present application, the design NP ratio is not necessarily in the range of 1.1~1.5. If it is for special needs, the design NP ratio can also be higher or lower. The design NP ratio is limited to 1.1~1.5 here only because the design range of the NP ratio is usually 1.1~1.5.

[0044] Alternatively, according to experimental verification, it is found that when k is 8.5%~12%, it can better improve the problems of edge lithium deposition and bulging.

[0045] like Figure 2 and Figure 3 As shown, the method for preparing the positive electrode sheet 10 of the laminated lithium battery provided in the embodiment of the present invention comprises:

[0046] A thinning groove is provided on each side of the active layer 12 of the positive electrode sheet 100 obtained after rolling, and the thinning groove corresponding to the thinning groove is used to form a small thickness area 12b;

[0047] The thinning grooves include an edge thinning groove 111 and a middle thinning groove 112, wherein the edge thinning groove 111 is located at the edge of the active layer 12 of the positive electrode sheet 100, and the middle thinning groove 112 is located at the non-edge of the positive electrode sheet 100;

[0048] Punching is performed along the length direction of the middle thinning groove 112 to obtain a plurality of finished positive electrode sheets 10 .

[0049] The present application increases the edge NP ratio by providing thinning grooves on the initial positive electrode sheet after rolling, and has the characteristics of easy operation and construction; this method can improve the lithium deposition and bulging problems by sacrificing a small amount of capacity; since the thickness of the active layer will no longer change after rolling, the thinning of the active layer after rolling also has the characteristic of controllable thinning accuracy, so the preparation method provided by the embodiment of the present invention can effectively improve the lithium deposition and bulging problems of the battery.

[0050] Optionally, the width L1 of the edge thinning groove 111 is 4-6 mm (eg, 4 mm, 5 mm, or 6 mm); the width L2 of the middle thinning groove 112 is 8-12 mm (eg, 8 mm, 10 mm, or 12 mm).

[0051] Optionally, the punching is performed along the center line of the middle thinning groove 112 .

[0052] Optionally, the middle thinning groove 112 is rectangular in shape when visible on the surface of the active layer 12, and the cross-section of the middle thinning groove 112 perpendicular to the surface of the active layer 12 is rectangular, isosceles triangle, semicircle or semi-ellipse. The cross-section is preferably rectangular.

[0053] The laminated lithium battery provided in the embodiment of the present invention comprises the positive electrode sheet 10 provided in the embodiment of the present invention. Since the laminated lithium battery comprises the positive electrode sheet 10 provided in the present invention, it has the characteristic of long service life.

[0054] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0055] Example 1

[0056] Target battery: 50Ah soft-pack laminated lithium-ion, the weight percentage ratio of each component in the active layer of the positive electrode is: positive electrode active material (lithium iron phosphate) 93.7%, adhesive (polyvinylidene fluoride) 3.24%, dispersant (polyvinyl pyrrolidone) 0.57%, conductive agent (carbon nanotube) 0.57%, conductive agent (carbon black) 1.92%; the weight percentage ratio of each component in the active layer of the negative electrode is: active material (graphite) 95.4%, conductive agent (carbon black) 1.50%, dispersant (sodium carboxymethyl cellulose) 1.30%, adhesive (styrene-butadiene rubber) 1.80%.

[0057] The surface density of the initial positive electrode sheet after rolling is 32.00 mg / cm 2 , thickness is 148μm, current collector thickness is 13μm, the mass ratio of positive electrode active material to active layer is 93.7%, gram capacity is 144mAh / g, target positive electrode sheet active layer length is 188mm, target positive electrode sheet active layer width is 160mm, target positive electrode sheet normal thickness area length is 178mm, width is 150mm; negative electrode sheet surface density after rolling is 16.31mg / cm 2 , the thickness of the negative electrode sheet is 122μm, the thickness of the current collector is 6μm, the mass ratio of the negative electrode active material to the active layer is 95.40%, the gram capacity is 330mAh / g, and the designed NP ratio is 1.15.

[0058] Substituting into the formula for calculation, k is 10.59%; the difference H between the normal thickness area 12a and the small thickness area 12b is about 7.15 μm (ie, the depth of the thinning groove is about 7.15 μm).

[0059] According to the above H value, thinning grooves with rectangular cross sections in the horizontal and vertical directions are cut on both sides of the pole piece after rolling and before punching.

[0060] The edge thinning groove 111 has a width of 5 mm and a depth of 7.15 μm, and the middle thinning groove 112 has a width of 10 mm and a depth of 7.15 μm;

[0061] Punching is performed along the center line of the middle thinning groove 112 to obtain a plurality of positive electrode sheets 10, each positive electrode sheet 10 having a width of 188 mm;

[0062] The positive electrode sheet 10 is assembled into a laminated soft-pack battery.

[0063] Example 2

[0064] This embodiment is basically the same as the embodiment 1, except that the depth of the thinning groove is not determined by a formula, but the thinning ratio coefficient and depth are directly set, k is taken as 10%, and the thinning depth is 6.8 μm.

[0065] Embodiment 3, 4

[0066] Embodiments 3 and 4 are basically the same as embodiment 2, except that the cross-sections of the intermediate thinning grooves 112 are inverted triangles (such as Figure 4 as shown), semicircular (as shown Figure 5 as shown).

[0067] Embodiments 5 to 10

[0068] Embodiments 5 to 10 are substantially the same as embodiment 2, except that the widths of the middle thinning groove 112 are 4 mm, 6 mm, 8 mm, 12 mm, 14 mm, and 16 mm, respectively, and the width of the edge thinning groove 111 is 1 / 2 of the width of the middle thinning groove 112 .

[0069] Embodiments 11 to 16

[0070] Examples 11 to 16 are basically the same as Example 2, except that the depth of the thinning groove is not determined by a formula, but the thinning ratio coefficient and depth are directly set, and the depths are 1.36 μm, 2.72 μm, 4.08 μm, 5.44 μm, 8.16 μm, and 9.52 μm, respectively.

[0071] Since the thinning ratio coefficient and depth of Examples 11 to 16 are calculated based on Example 2, the exact value of the thinning depth when k is 10% in Example 2 is 6.75 μm, and the value retained to one decimal place is 6.8 μm. Therefore, the depth and thinning ratio coefficient of Examples 11 to 16 calculated based on the thinning depth of Example 2 do not completely correspond to the formula H=k(ab) / 2, and there is a slight error between the depth and the thinning ratio coefficient.

[0072] Comparative Example

[0073] This comparative example is basically the same as Example 1, except that no thinning groove is provided during the manufacturing process, and the size of the prepared positive electrode sheet 10 is the same as that of Example 1.

[0074] Experimental example

[0075] The soft-pack batteries prepared in various embodiments and comparative examples were cycled 6000 times, and the average expansion rate 2 mm inward from the edge was tested.

[0076] Each group of batteries has 10 pieces, and the test average value is taken. The cycle conditions are as follows:

[0077] 1) 25℃, 0.5C constant current discharge to 2.5V;

[0078] 2) 25℃, leave for 10min;

[0079] 3) 25℃, 1C constant current and constant voltage charging to 3.65V, cut-off current 0.05V;

[0080] 4) 25℃, let stand for 10min;

[0081] 5) 25℃, 1C constant current discharge to 2.5V;

[0082] 6) 25℃, set aside for 20 minutes;

[0083] 7) Repeat steps 3-6 until the cycle reaches 6000.

[0084] The battery performance data obtained from Examples 2 to 4 and the comparative example are compared, and the results obtained are shown in Table 1:

[0085] Table 1 Data comparison of some embodiments and comparative examples

[0086]

[0087] It can be seen from Table 1 that when the edge thickness of the active layer is smaller (that is, a thinning groove is opened), it is helpful to reduce the expansion rate, among which the cross-sectional shape of the middle thinning groove is better than an inverted triangle, and an inverted triangle is better than a semicircle.

[0088] The battery performance data obtained by Example 2, Examples 5 to 10 and the comparative example are compared, and the results obtained are shown in Table 2:

[0089] The battery performance data obtained by Example 2, Examples 5 to 10 and the comparative example are compared, and the results obtained are shown in Table 2:

[0090] Table 2 Data comparison of some embodiments and comparative examples

[0091]

[0092] As can be seen from Table 2, the expansion rate of the positive electrode sheets prepared in various embodiments of the present invention after being assembled into batteries is significantly lower than that of the comparative example. The width of the small thickness area of ​​the positive electrode sheet should not be too small, otherwise it cannot effectively control the bulging caused by lithium deposition. The width of the small thickness area of ​​the positive electrode sheet should not be too large, otherwise it will inevitably lead to a large capacity loss.

[0093] Since the design capacity usually has redundancy and a certain error is allowed in actual production, a small capacity loss caused by edge thinning is usually allowed. When the width of the small thickness area of ​​the positive electrode sheet is 4~6mm, the capacity loss rate is less than 1.30%, and the average expansion rate is less than 7%. This width range makes the overall performance of the positive electrode sheet optimal.

[0094] Table 3 Data comparison of some embodiments and comparative examples

[0095]

[0096] As shown in Table 3, the expansion rate of the positive electrode sheets prepared in various embodiments of the present invention after being assembled into batteries is significantly lower than that of the comparative example. The expansion rate decreases with the increase of the depth of the thinning groove, but when it decreases to a certain extent, the decrease is no longer obvious. If the thinning depth is too deep, it will undoubtedly cause more unnecessary capacity loss.

[0097] Since the design capacity usually has redundancy and a certain error is allowed in actual production, a small capacity loss caused by edge thinning is usually allowed. Preferably, in order to further ensure that the capacity loss is within the allowable error range and avoid unnecessary capacity loss, the cutting depth with a capacity loss rate of less than 1.30% is preferred, that is, the depth is approximately less than 8.16μm. More preferably, in order to ensure unnecessary capacity loss and have a significantly better low expansion rate, the thinning depth is around 6.8μm, for example, 5.44~8.16μm. At this time, correspondingly, the thinning depth proportional coefficient k is 8.5~12%.

[0098] The thinning ratio coefficient of Example 1 is calculated by a formula, which is in the range of 8.5-12%, close to the middle value. Therefore, when processing the positive electrode sheet, the optimal thinning depth can be determined by the formula provided by the present invention.

[0099] In summary, the thickness of the positive electrode sheet provided by the present invention is smaller at the edge of the active layer than at the non-edge. Within the range of edge lithium deposition in the later stage of the cycle, the thickness of the edge is reduced by thinning design, and a slightly larger edge NP ratio suitable for the later stage can be obtained, which can effectively improve the problems of edge lithium deposition and bulging edge after the cycle of the laminated lithium battery.

[0100] The preparation method provided by the present invention increases the edge NP ratio by opening thinning grooves on the initial positive electrode sheet after rolling, and has the characteristics of easy operation and construction; the method can improve the lithium deposition and bulging problems by sacrificing a small amount of capacity; because the thickness of the active layer will no longer change after rolling, the thinning of the active layer after rolling also has the characteristic of controllable thinning accuracy, so the preparation method provided by the embodiment of the present invention can effectively improve the lithium deposition and bulging problems of the battery.

[0101] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode sheet of a laminated lithium battery, characterized in that: The positive electrode sheet includes a current collector and an active layer arranged on two opposite sides of the current collector; Each active layer comprises a normal thickness region and a small thickness region, wherein the small thickness region is located at the edge of the active layer, and the thickness of the normal thickness region is greater than the thickness of the small thickness region; The width of the small thickness area is 4-6 mm; The preparation method comprises: opening a thinning groove on each active layer of the positive electrode sheet obtained after rolling, wherein the thinning groove corresponding to the thinning groove is used to form the small thickness area; The difference in thickness between the normal thickness area and the small thickness area is H, and H is determined by the following formula: H=k(ab) / 2, where a is the thickness of the positive electrode sheet in the normal thickness area, b is the thickness of the current collector, and k is the thinning depth proportionality coefficient; k=[(A1*w1*R1) / (A2*w2*R2)]*[1-(S0*(1-1%)-S1) / S2], A1 is the negative electrode surface density, unit mg / cm 2 ; w1 is the proportion of negative electrode active material; R1 is the negative electrode capacity in gram, unit mAh / g; A2 is the surface density of the normal thickness area, unit mg / cm 2 ; w2 is the proportion of positive electrode active material; R2 is the positive electrode capacity in grams, unit mAh / g; S0 is the active layer area of ​​the positive electrode sheet, unit mm 2 ; S1 is the normal thickness area, unit: mm 2 ; S2 is the area of ​​the small thickness region, unit: mm 2 ; The skived grooves include edge skived grooves and middle skived grooves, wherein the edge skived grooves are located at the edges of the active layer of the primary positive electrode sheet, and the middle skived grooves are located at the non-edges of the primary positive electrode sheet; Punching is performed along the length direction of the intermediate thinning groove to obtain a plurality of finished positive electrode sheets.

2. The preparation method according to claim 1, characterized in that: The designed NP ratio of the positive electrode sheet is 1.1-1.5, and the designed NP ratio refers to the designed value of the ratio of the negative electrode capacity to the positive electrode capacity of the battery.

3. The preparation method according to claim 1, characterized in that: The difference between the normal thickness area and the small thickness area is H=k(ab) / 2, where a is the thickness of the positive electrode sheet in the normal thickness area, b is the thickness of the current collector, and k is the thinning depth proportional coefficient, which is 8.5%~12%.

4. The preparation method according to claim 1, characterized in that: The width of the edge thinning groove is 4-6 mm; the width of the middle thinning groove is 8-12 mm.

5. The preparation method according to claim 4, characterized in that: The punching is performed along the center line of the middle thinning groove.

6. The preparation method according to claim 1, characterized in that: The shape of the intermediate thinning groove visible on the surface of the active layer is a rectangle, and the shape of the cross section of the intermediate thinning groove perpendicular to the surface of the active layer is a rectangle, an isosceles triangle, a semicircle or a semi-ellipse.

Citation Information

Patent Citations

  • Preparation method of battery pole piece, die head gasket and battery

    CN113130839A

  • Electrode assembly, battery and electric equipment

    CN116454415A